Multiferroic Heterostructures: Ultraflexible and Malleable Fe/BaTiO3 Multiferroic Heterostructures for Functional Devices (Adv. Funct. Mater. 16/2021). (15th April 2021) - Zhao, Yanan; Peng, Renci; Guo, Yunting; Liu, Zhijie; Dong, Yongqi; Zhao, Shishun; Li, Yaojin; Dong, Guohua; Hu, Yue; Zhang, Junwei; Peng, Yong; Yang, Tiannan; et al.
Abstract : In article number 2009376, Zhenlin Luo, Ming Liu, and co‐workers present ultra‐flexible and malleable Fe/BaTiO3 heterostructures with a good multiferroic pro perty, which show a large thermally driven magnetoelectric coupling effect by avoiding the substrate clamping effect, as well as other fascinating flexible‐tuning interfacial phenomena. The research provides broader opportunities for low‐power‐driven flexible applications, and contributes to the community of flexible oxide materials application in a significant manner.